Internet of Things Untuk Mitigasi Bencana Tanah Longsor Studi kasus : Jalan lintas Sumbar Riau - Noviardi Noviardi; Dilson Dilson (Ikatan Ahli Informatika Indonesia, 2018)
West Sumatra is one of the provinces that is most at risk of landslide, due to the condition of the area which is passed by cluster of hill barisan, there are at least 23 point of slope prone to landslide which is in West Sumatera traffic lane to Riau. Supported by high rainfall, the potential for disaster is very high, in 2016 a landslide occurred in 13 points that resulted in the loss of life and swept away the vehicle. Until now there has been no concrete steps in applying technology in disaster management. Based on Law No. 24 of 2007 on disaster management, where in Article 44 paragraph 1 and 2 stages of disaster management allows integration with the technology of the Internet of Thing (IoT), Smart monitoring System is the application of IoT technology. This technology is used to streamline the observation of landslide disaster symptoms to reduce the risks posed by the disaster. This research uses Desaign Science Reaserch Method (DSRM) method. This research will reveal how appropriate models for the implementation of IoT for landslide mitigation. In this study found that all stages of disaster management can be integrated with IoT Technology